Sustainability Assessment and Strategies Development for Individual LivestockRearing in Cikedung District, Indramayu Regency, West Java (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Individual livestock farmers in Cikedung Subdistrict, Indramayu Regency, play a crucial role in supporting national beef production. However, they encounter significant challenges, including limitedtechnological access, weak management efficiency, restricted market access, and minimal institutionalsupport. This study aims to evaluate the sustainability of individual rearing systems using the Multidimensional Scaling (MDS) analysis method through the Rap-UPTS model, covering five dimensions:economic, socio-cultural, ecological, legal-institutional, and technological-infrastructure. A total of 15respondents were involved, and the analysis employed leverage and Monte Carlo techniques. Findingsrevealed a “less sustainable” status, with the highest score in the ecological dimension (49.80) and thelowest in the legal-institutional dimension (37.61). The model was deemed valid, with a stress value of0.133 and an R² of 0.95. Strengthening institutional support and enhancing human resource capacity arekey strategies for improving sustainability in smallholder livestock systems.